TEACHING WRITING NARRATIVE TEXT USING PICTURES TO THE FIRST SEMESTER STUDENTS OF FACULTY OF SOCIAL AND POLITICS UNIVERSITY OF TULUNGAGUNG - Herminingsih, Dwi Ima (Jurnal BONOROWO, 2013)
People can communicate their ideas, thoughts and feeling to other people in oral or written form of language. The communication mostly can run well if it is done by using a native language or a language that people understand best. By contrast, a lot of people usually feel difficult when they must express their opinions and feelings in speaking or writing by using a foreign language or a language that they do not master. In the con text of Indonesia,particularly at faculty of Social and Politics, University of Tulungagung, English is one foreign language that the majority students do not master yet. It is not surprising that they are less competent in English writing skill. They are hindered by lack knowledge of grammar,vocabulary and do not have sufficient ability to organize ideas in a good writing.Under this regard, helpful teaching media like pictures are supposed to be a possible prescription as scaffolding to guide them producing well organized writing. Further, the use of pictures can increase the studentsâ achievements in writing ability.